Teologi Pembenaran oleh Iman menurut Paulus dalam Surat Galatia 3:1-12 dan Kontekstualisasi dalam Kehidupan Gereja HKBP - Lumongga Debora Tambun (Collecta: Jurnal Teologi dan Tradisi Kristen, 2024)
This article critically examines the Apostle Paul's doctrine of justification by faith as articulated in Galatians 3:1-12 and seeks to contextualize it within the life and ministry of the HKBP Church. In Galatians 3:1-12, Paul addresses the misconception among the Galatians, who believed that justification could be achieved through good works rather than faith in Christ. Paul emphasizes that justification is not obtained through adherence to the law or the performance of good deeds but solely through faith in Christ. This doctrine aligns with the theological principles of faith and salvation as outlined in the HKBP's Agenda and Confession of Faith. However, this concept has not been fully understood or embraced by the broader HKBP congregations. Many still prioritize tradition and good works, often doubting the assurance of salvation, which can lead to a lack of genuine belief. Utilizing a qualitative research methodology, this study seeks to clarify the doctrine of justification to prevent doctrinal misinterpretations that could undermine faith and religious practices within the church. Furthermore, the paper explores how the theology of justification by faith can be effectively integrated into HKBP church practices.